2020
DOI: 10.31603/burrev.3964
|View full text |Cite
|
Sign up to set email alerts
|

Urgensi Pembentukan Undang-Undang Fintech sebagai Upaya Legalisasi Penyelesaian Sengketa Transaksi Fintech di Indonesia

Abstract: Perkembangan industri fintech di era revolusi industri 4.0 menjadi tren transaksi keuangan di tengah-tengah masyarakat dunia saat ini, termasuk di Indonesia. Legalitas yang memadai sangat diperlukan untuk mengatasi berbagai permasalahan yang diakibatkannya. Penelitian ini bertujuan mengidentifikasi urgensi pembentukan undang-undang fintech sebagai upaya legalisasi penyelesaian sengketa transaksi fintech di Indonesia. Penelitian ini menggunakan metode Legal Research dengan pendekatan kualitatif. Hasil yang dipe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…OJK's limitations in overcoming problems that occur in the fintech business require the promulgation of more specific regulations like the law so that these business actors get legal protection and assurance. (Dakum & Praja, 2020)…”
Section: C) Increase Efficiency and Effectivenessmentioning
confidence: 99%
“…OJK's limitations in overcoming problems that occur in the fintech business require the promulgation of more specific regulations like the law so that these business actors get legal protection and assurance. (Dakum & Praja, 2020)…”
Section: C) Increase Efficiency and Effectivenessmentioning
confidence: 99%
“…Seperti pengawasan terhadap konsistensi berjalannya anggaran dasar lembaga dan pengajuan self assessment system oleh penyelenggara yang berisikan laporan keuangan dan kegiatan usaha yang seharusnya ditinjau oleh Otoritas Jasa Keuangan secara bekala. Pengawasan operasional yang kurang optimal disebabkan minimnya kordinasi antar otoritas, terdapat pula hambatan regulasi lintas sektor yang kurang mendukung proses pengawasan, dan kurangnya infrastruktur yang menunjang pengawasan oleh OJK (Ernama Santi et al, 2017) (Dakum & Asari, 2020).…”
Section: Progresifitas Undang-undang Ite Dan Pojk Pada Transaksi Berb...unclassified
“…A study conducted by Facebook and Good and The Company revealed that the number of digital consumers in Indonesia is expected to grow from 119 million in 2019 to 137 million in 2020. Bank Indonesia also estimates that crypto currency translation transactions will increase by 32.3% from Rp201 trillion in 2020 to Rp266 trillion in 2021 (Dakum & Asari, 2020;Putri, Komara, & Setyowati, 2021) alternative for the community, especially during the COVID-19 pandemic, especially for small and medium enterprises. Fintech has a very important role in the development of SMEs.…”
Section: Introductionmentioning
confidence: 99%